2006
DOI: 10.1038/sj.jp.7211511
|View full text |Cite
|
Sign up to set email alerts
|

Equations to support predictive automated postnatal growth curves for premature infants

Abstract: Growth charts are used in pediatric medicine to plot anthropomorphic measurements over time, serving as a screen for diseases related to a patient's nutritional and general health status. Whereas reference data for term infants are available from the Center for Disease Control, reference data for premature infants in a neonatal intensive care unit have not been established. Predictive curves for preterm patients, which are based on a patient's postmenstrual age and anthropomorphic measurements at birth, cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The overall proportion of preterm with poor weight gain observed in this study was high. Furthermore the observed average weight gain is below the goal for preterm weight gain (≥ 15 grams/kg/day) estimated to replicate the growth velocity of a normal foetus during third trimester of pregnancy (4,(11)(12)(13)(14). Poor weight gain was observed more among early preterm compared to late preterm infants, although this was not statistically signi cant, it may be a re ection of poor feeding as a result of feeding intolerance and also the practice in our unit during the study period of delaying initiation of feeds for at least 24 hours for this category of neonates.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The overall proportion of preterm with poor weight gain observed in this study was high. Furthermore the observed average weight gain is below the goal for preterm weight gain (≥ 15 grams/kg/day) estimated to replicate the growth velocity of a normal foetus during third trimester of pregnancy (4,(11)(12)(13)(14). Poor weight gain was observed more among early preterm compared to late preterm infants, although this was not statistically signi cant, it may be a re ection of poor feeding as a result of feeding intolerance and also the practice in our unit during the study period of delaying initiation of feeds for at least 24 hours for this category of neonates.…”
Section: Discussionmentioning
confidence: 83%
“…Postnatal growth pattern in preterm and LBW neonates is often characterized by initial physiological weight loss in the rst 7 days of life of approximately 7-15% of their birth weight. Thereafter recovery occurs with increase in body weight from around 10 th to 21 st day of life (3,4). However, differences in weight trends have been observed with respect to the age of the preterm, being more marked amongst early and extreme preterm as compared to late preterm (5).…”
Section: Introductionmentioning
confidence: 99%
“…The overall proportion of preterm with poor weight gain observed in this study was high. Furthermore the observed average weight gain is below the goal for preterm weight gain (≥ 15 g/kg/day) estimated to replicate the growth velocity of a normal foetus during third trimester of pregnancy [ 4 , 11 14 ]. Poor weight gain was observed more among early preterm compared to late preterm infants, although this was not statistically significant, it may be a reflection of poor feeding as a result of feeding intolerance and also the practice in our unit during the study period of delaying initiation of feeds for at least 24 h for this category of neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal growth pattern in preterm and LBW neonates is often characterized by initial physiological weight loss in the first 7 days of life of approximately 7-15% of their birth weight. Thereafter recovery occurs with increase in body weight from around 10th to 21st day of life [3,4]. However, differences in weight trends have been observed with respect to the age of the preterm, being more marked amongst early and extreme preterm as compared to late preterm [5].…”
Section: Introductionmentioning
confidence: 99%
“…A non-linear model by Riddle et al 20 was demonstrated to be extremely accurate in predicting growth in NICU infants. This model very closely fit growth patterns from NICU infants with BW 500–2700g using a piecewise function consisting of a parabola from birth until regaining BW and an exponential function after regaining BW.…”
Section: Discussionmentioning
confidence: 99%